CD5‐positive diffuse large B cell lymphoma arising from a CD5‐positive follicular lymphoma - Vassallo, José (BMJ Group, 2007)
Follicular lymphoma (FL) is a neoplasm originating from germinal centre cells, corresponding to 25–40% of non‐Hodgkin's lymphomas. Transformation into diffuse large B cell lymphoma (DLBCL) occurs in about one‐third of cases. CD5 is expressed in B‐chronic lymphoid leukaemia/small lymphocytic lymphoma and mantle cell lymphoma, but can rarely be expressed in conjunction with CD10 in well‐documented cases of FL. In this report one case of grade 1 FL is described, which transformed into a DLBCL 6 months after initial diagnosis, with both tumours expressing CD5. In both specimens, neoplastic cells were strongly positive for CD20, CD79a, bcl‐2, bcl‐6 and CD5 in virtually all cells. CD10 was strongly positive in initial specimens and weakly positive in the DLBCL. Investigation using the PCR confirmed the derivation of the DLBCL from the FL as they presented the same immunoglobulin heavy chain gene rearrangement and the same BCL2‐J(H) break point.